Evaulation of varicocelectomy efficacy in primary and secondary infertile men - F. A. Akilov; Sh. T. Muxtarov; A. B. Shomarufov; Sh. A. Abbosov; Sh. I. Giyasov; D. H. Mirkhamidov; Sh. X. Gulomov (Вестник урологии, 2025)
Introduction. Varicocele is one of the main causes of subfertility in men with primary and secondary infertility.   Objective. In this study, we compared the initial semen parameters and the effectiveness of varicocelectomy in men with primary and secondary infertility.   Materials & methods. 100 men suffering from primary infertility (PI) and secondary infertility (SI) and having varicocelectomy were recruited. Patients were divided into 2 groups. Group 1 included 58 men with PI and the group 2 42 men with SI. Preoperative clinical characteristics and semen parameters before and after varicocelectomy were analyzed and compared between groups.   Results. Analysis revealed that the mean age of patients of the group 1 was significantly lower (p < 0,001) and duration of infertility was accurately shorter (p < 0,01) than those of group 2. Main semen parameters increased significantly in group I (e. g., sperm concentration increased by 50 %, from 62,2 ± 8,7 to 93,5 ± 10,0 M/ml and total motile sperm count increased by 113 %, from 76,7 ± 17,1 to 163,4 ± 27,8 M p < 0,05), while in group 2 only % of progressive motile sperm increased significantly (by 107 %, from 13,5 ± 2,6 to 28,0 ± 5,2 % p < 0,05). We identified significant difference in varicocelectomy efficacy between group 1 and group 2 in change of total motile sperm count (by 113 % vs. 74 % respectively, p < 0,01). We also revealed discrepancy between groups in correlation ratio (r) between initial and post-surgical percentage of progressive motile sperm.   Conclusions. Patients with SI were older and had longer infertility period. Varicocelectomy resulted in significant semen parameters improvement in patients with PI. In patients with SI only a percent of progressively motile sperm improved significantly. It shows that male age and infertility duration may negatively affect varicocelectomy outcomes in male subfertility treatment.